2022
DOI: 10.1117/1.jei.31.5.051412
|View full text |Cite
|
Sign up to set email alerts
|

(Retracted) Image restoration and quantitative metallographic tissue based on machine vision

Abstract: . In recent years, with the development of computer image processing technology and quantitative metallography, quantitative metallographic analysis and image restoration based on machine vision image processing have attracted extensive attention. To deeply study the special ability of machine vision technology in metallographic image restoration and quantitative analysis, we adopt a model construction method, parameter design method and comparative analysis method to collect samples and analyze the machine vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Experimental findings demonstrated that their method achieved a recognition rate 5.69% higher than Method 3, with an overall recognition rate of 98.65%, surpassing Method 3 by 5.1%. These results underscore the effectiveness of image classification algorithms and affirm the system's efficacy in metallographic tissue image restoration and quantitative analysis [6] . Ye, H. et al…”
Section: Literature Reviewsupporting
confidence: 57%
“…Experimental findings demonstrated that their method achieved a recognition rate 5.69% higher than Method 3, with an overall recognition rate of 98.65%, surpassing Method 3 by 5.1%. These results underscore the effectiveness of image classification algorithms and affirm the system's efficacy in metallographic tissue image restoration and quantitative analysis [6] . Ye, H. et al…”
Section: Literature Reviewsupporting
confidence: 57%